Indigenous Feminism for American Indigenous Women Portrayed on The Plague of Doves by Erdrich (Rainbow : Journal of Literature, Linguistics and Culture Studies, 2023)
Legitimacy of women existences captured diverse and compound through the lens of cultural and social background. In the course of history, American Indigenous Women elucidated their identity articulation following the West at the hand of feminism. However, ‘white’ feminism is not in the position to accommodate the unique characteristics of American Indigenous Women. Their social contour and cultural commandment of which giving a rise out of their position and power cried out for suitable paradigm. Indigenous feminism as perspective from and to Indigenous Women would serve to scrutinize women empowerment, aspiration and self-actualization of American Indigenous Women. The article as presented is part of the dissertation analysis within the title Cultural Memory and Demystification of American Native Women’ Position. The analysis of this research is a library based employing the novel from Indigenous female author, Louise Erdrich, entitled The Plague of Dove. In the discussion, the portrayal and representation of certain social and cultural phenomena have been captured and put into consideration as Indigenous Women’s struggle in this modern days. The regulation and also power to determine Indigenous Women’ identity have been strictly limited due to the presence of oppression. The unique of this research laid on the characteristics of the source of oppression in which is in a cooperated linkage within the paradigm employed which is Indigenous feminism. As there are diverse social and traditional elements brought, this research went deep in to the intersectionality studies, focusing on the sexism, racism and colonialism issues predominantly captured as the root of the oppression and discrimination against Indigenous Women.